The proliferation and differentiation responses of adult mouse neural stem cells in vitro - Chou, Robert Chang-Chih (2015)
Recent studies have shown that the adult brain retains a population of stem cells in specific locations. Adult neural stem cells (NSCs) from the subventricular zone of the lateral ventricle have self-renewing and differentiation capability. These NSCs are capable of differentiating into astrocytes, oligodendrocytes and neurons in vitro. Study the proliferation and differentiation capability of the adult NSCs would provide a resource for developing new treatments for neurodegenerative diseases in the future. Retinoic acid has been described to promote neuron formation from the several different types of stem cell in vitro. Recently, a novel synthetic analogue EC23 has been released. However, the impact of EC23 on neuron formation and cell growth remain unclear. This project focuses on comparing the pro-neurogenic capability and impact on cell growth and cell cycle of EC23 with Retinoic acid and preliminary evaluating the character of PPARγ in Retinoid-induced neuron formation by using PPARγ agonist Rosiglitazone.